(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Covid-19 is a disease that caused great havoc worldwide, not being prepared to combat such a disease caused, various economic and educational affectations, the latter being the most affected, because the measures taken were the suspension of classes and other cases of the current school year. Therefore, the use of ICTs is an important step for the development and recovery of society due to the effects of the pandemic, because methods were used to be able to have a distance education using tools and technological applications in which effective communication could be had between the teacher and the student. Through this research, the objective is to describe how tics in relation to education helped society to stand out from a pandemic that to this day still has sequelae within the various social aspects that make up a society, with the help of a descriptive-documentary method, it will seek to support the basis of this research